Metode User Centered Design dalam Pemodelan Aplikasi Pendamping Ibu Berdasarkan Buku KIA untuk Monitoring Ibu Hamil - Izzati Muhimmah; Sahriani; Yasmini Fitriyati (LPPM Hang Tuah Pekanbaru, 2023)
Maternal and fetal health is one of the most important indicators of health status in the community. However, in reality, the mortality rate for pregnant women in Indonesia is still relatively high as happened in Bantul Regency, DIY. Contributing factors include limited health service facilities and a lack of communication between pregnant women and cadres or midwives about their condition, resulting in delays in recognizing danger signs of pregnancy. Therefore, efforts are needed to overcome these problems, one of which is by creating a mother companion application service (API). The purpose of this study was to make a model of a mother's assistant application (API) based on the MCH book using the User Centered Design (UCD) method for monitoring pregnant women. In this study. The results presented are in the form of a prototype API service information system, where this system can help pregnant women to find out the history of previous examinations, see health articles needed during pregnancy, and when an emergency occurs, pregnant women can use the emergency button so they can quickly connect to a companion, cadres, and midwives nearby. the results of this information system design are expected to make it easier during the pregnancy process. Therefore, it can be concluded that the creation of a mother companion application modeling (API) using the UCD method is effective in helping when carrying out the prototype design process because the user directly plays an active role in providing suggestions so that the requirements for the desired system can be fulfilled.